“ESTUDIO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE VINO DE TUNA EN LA CIUDAD DE LOJA” - Pontón Ramón, Luis Guillermo (2019)
The project was based on the study to determine the feasibility of implementing a company producing and marketing tuna wine, whose industrial process guarantees to preserve its healing properties and requirements for its commercialization and consumption. In order to comply with this main objective, methods, techniques and procedures were used to investigate, develop and verify the veracity of the project. The methods used were: inductive, deductive, analytical, descriptive and mathematical. In addition, the following techniques were applied: direct observation, survey and interview. Within the first objective is the market study, for this purpose surveys were conducted to 381 families with favorable results where, 91% of families surveyed consume wine, 87% prefer sweet wine and 96% of families who consume wine sweet manifest that they would be our customers The offer in the market was determined through an interview with local producers and marketers, concluding the nonexistence of the tuna wine, since all the wines that they commercialize are of traditional raw material grape must, mostly imported, where a wine was obtained. total of 15,600 bottles per year plus 10% of home production. In this way the unmet demand was determined giving a total of 402.655 bottles of wine, finally through the market study the marketing plan of the company was established through strategies according to the product, place and distribution of the product, the price and advertising to enter to compete in the market Likewise, the technical study was conducted where the size, location, requirements of the company, its production process were studied and 100% of the installed capacity was established, where 25,480 annual units of prickly pear wines are produced in a presentation 5 of 750 ml. In the engineering of the project the productive process was defined, where it is established that for every 6 days 70 bottles of tuna wine are produced It was defined through the administrative study that the company will be limited liability under the name of "GUIBE CIA. LTDA.¨ which will have 2 partners where they will provide a social capital and also be financed by a bank loan to cover the entire investment, in addition to a good organizational development organizational charts and functional manual for all staff. With the financial study, it was determined that in order to implement the company, own capital of $ 23,070.25 is needed, equivalent to 50% of the investment and external capital of $ 23,070.25, with an annual interest of 11%, which represents the other 50 % of the investment, which will be financed by the bank BAN ECUADOR. After the cost analysis was carried out, it was determined that the price of the product for the first year is $ 5.50 for our intermediaries and $ 6.00 price to the final consumer Finally the financial evaluation was carried out and in this way we could know the feasibility or not of the project through financial indicators such as; The Net Present Value (NPV) where a positive result of $ 34,860.65 was obtained, the Internal Rate of Return (IRR) was 33.05% which is greater than the opportunity cost, the Cost Benefit Ratio (RBC) obtained that for each dollar invested you get 25 cents of return, the Period of Recovery of Capital (PRC), it was established that the investment will recover in 3 years, 5 months and 26 days and finally the analysis of sensitivity with increase in costs it is 10.26% and the sensitivity analysis with decrease in income is 8.33%, so the project is not sensitive to these variations that may influence profitability. Because of the above, it is shown that the implementation of the investment project is feasible